Systematic Review: Intervensi Nonfarmakologis Manajemen Demam pada Anak di Rumah Sakit - Anggi Luckita Sari; Nurul Istiqomah (Universitas Muhammadiyah Klaten, 2026)
Fever is a physiological response of the body to infection, characterized by an increase in body temperature above the normal range. This condition is common among children and is one of the primary reasons parents seek emergency medical care for their children in hospitals. The management of fever in children can generally be divided into two approaches: pharmacological treatment using antipyretics and non-pharmacological therapy. Non-pharmacological techniques are considered an effective alternative to help lower body temperature safely and naturally. However, many healthcare professionals remain uncertain and inconsistent in implementing or recommending non-pharmacological methods for managing fever in children. Therefore, this study aims to synthesize various articles discussing non-pharmacological fever management techniques in hospitalized children. Literature searches were conducted through several databases, including Google Scholar, ScienceDirect, and Semantic Scholar, covering publications from 2011 to 2021. The article selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. From a total of 18,693 identified articles, only 8 met the inclusion criteria and were further reviewed. The findings revealed that several non-pharmacological interventions such as cold compresses, warm sponge baths, tepid sponge techniques, and warm foot immersion are effective in reducing fever in children during hospital care. Overall, these methods provide practical and safe alternatives that can be used alongside pharmacological interventions to enhance fever management in pediatric patients.